Correction: Titanium aminophosphates: synthesis, characterization and crystal violet dye degradation studies. Issue 114 (1st December 2016) - Rajini, Anumula; Adepu, Ajay Kumar; Chirra, Suman; Siliveri, Suresh; Venkatathri, Narayanan
Abstract : Correction for 'Titanium aminophosphates: synthesis, characterization and crystal violet dye degradation studies' by Anumula Rajini et al., RSC Adv., 2016, 6, 507–514.